The shape of the extragalactic cosmic ray spectrum from galaxy clusters - Harari, Diego Dario (2016)
We study the diffusive escape of cosmic rays from a central source inside a galaxy cluster to obtain the suppression in the outgoing flux appearing when the confinement times get comparable or larger than the age of the sources. We also discuss the attenuation of the flux due to the interactions of the cosmic rays with the cluster medium, which can be sizeable for heavy nuclei. The overall suppression in the total cosmic ray flux expected on Earth is important to understand the shape of the extragalactic contribution to the cosmic ray spectrum for E/Z < 1 EeV . This suppression can also be relevant to interpret the results of fits to composition-sensitive observables measured at ultra-high energies.